Prevalence rates and odds ratios of shoulder-neck diseases in different occupational groups. Issue 9 (September 1987) - Hagberg, M; Wegman, D H
Abstract : The aim of the present study was to evaluate the association and impact of occupational exposure and diseases of the shoulder and neck. Prevalence rates, odds ratios, aetiological fractions, and their confidence intervals were computed for pooled and non-pooled data of previous published reports. By comparison with office workers and farmers, dentists had an increased odds ratio for cervical spondylosis (two studies) and for shoulder joint osteoarthrosis. Meat carriers, miners, and "heavy workers" also had significantly higher rates of cervical spondylosis compared with referents. Compared with iron foundry workers, civil servants had a significant odds ratio (4.8) of cervical disc disease and a 0.79 aetiological fraction. Whether this was due to exposure or healthy worker effect was not clear. In four occupational groups with high shoulder-neck load an odds ratio of 4.0 was found for thoracic outlet syndrome with an aetiological fraction of 0.75. Rotator cuff tendinitis in occupational groups with work at shoulder level (two studies) showed an odds ratio of 11 and an aetiological fraction of 0.91. Keyboard operators had an odds ratio of 3.0 for tension neck syndrome (five studies). Unfortunately, owing to the scanty description of the work task, the exposure could be analysed only by job title. Examination of published reports shows clearly that certain job titles are associated with shoulder-neck disorders. High rates and aetiological fractions for rotator cuff tendinitis and tension neck syndrome suggest that preventive measures could be effective. Although job descriptions are brief, the associations noted suggest that highly repetitive shoulder muscle contractions, static contractions, and work at shoulder level are hazardous exposure factors. In reports of cross sectional studies of occupational shoulder-neck disorders presentation of age, exposure, and effect distribution may help for future meta-analysis.